Use of the term whole grain on the label of processed and ultra-processed foods based on cereals and pseudocereals in Brazil - Bez Batti, Érika Arcaro; Nascimento, Amanda Bagolin do; Geraldo, Ana Paula Gines; Fernandes, Ana Carolina; Bernardo, Greyce Luci; Proença, Rossana Pacheco da Costa; Uggioni, Paula Lazzarin (Frontiers in Nutrition, 2022)
There has been an increasing consumption of processed and ultra-processed foods, accompanied by growing concerns about the relationship between diet quality and health. Whole-grain foods, composed of cereals and pseudocereals, are recommended as part of a healthy diet, and food labeling is an important tool for consumers to identify the presence of whole grains in packaged foods. This study aimed to analyze the use of the term whole grain on the label of processed and ultra-processed foods based on cereals and pseudocereals sold in Brazil. Data were collected by a census of all food labels in a Brazilian supermarket. Foods were classified into eight groups according to Brazilian legislation and according to the presence or absence of the term whole grain. The prevalence of foods displaying the term whole grain or related expressions on the front label was assessed, and differences between groups were analyzed using Pearson's chi-squared test. Comparisons were also made in relation to the position of whole-grain ingredients in the ingredients list. The level of significance was defined as p < 0.05. The sample included 1004 processed and ultra-processed foods based on cereals and pseudocereals, 156 (15.6%) of which displayed the term whole grain and/or similar expressions on the front label. Of these, 98 (9.8%) contained the term whole grain, 25 (2.5%) displayed analogous expressions, and 33 (3.3%) contained the term whole grain concomitantly with analogous terms, identified in foods of the groups Bakery goods, bread, cereals, and related products and Sugars, sugary foods, and snacks. Half of the food products displaying the term whole grain or related expressions on the front label did not have a whole-grain ingredient listed in the first position of the ingredients list. The frequency of whole grains was even lower in subsequent positions. These findings reveal the existence of asymmetric information regarding the term whole grain or analogous expressions on the front label of cereal- and pseudocereal-based packaged foods. It is expected that these results will contribute to stimulating the food industry and regulatory bodies to improve the use of the term whole grain and related expressions on packaged food labels.